A understanding of the three dimensional microsurgical anatomical architecture of the temporal lobe with its functions - Atar, Murat; Kizmazoglu, Ceren; Uzunoglu, Inan; Cingoz, Ilker Deniz; Gurkan, Gokhan; Kaya, Ismail; Sozer, Gulden; Ozdilmac, Ahmet; Yuceer, Nurullah (Annals of Medical Research, 2021)
Aim: This study aimed to evaluate the human brain temporal lobe white matter pathways with respect to microsurgical anatomy, reveal the relationship between these white matter pathways, evaluate their functions, which are already known in the literature, and contribute to the literature to establish safe temporal region surgical interventions. Material and Methods: 10 specimens of postmortem human brain hemispheres were fixed in accordance with Klingler’s method. Subsequently, dissection of the temporal lobe white matter pathways was performed under a surgical microscope. Each stage of dissection was achieved using the technique of merging multiple focus images in high-quality three-dimensional images. Results: The data obtained in lateral-to-medial and medial-to-lateral dissections were compatible with the literature. Moreover, microsurgical three-dimensional architectural structure of temporal lobe white matter pathways has been clearly revealed. The horizontal and vertical segments of superior longitudinal fasciculus were detected. The limbic system, connection of central cores with the temporal lobe, temporal stems region, and relationship with other fiber systems have been shown in this study. The importance of the temporal stem and Meyer’s loop for safe interventions on temporal lobe has been noted. Conclusion: Temporal region white matter pathways should be handled in a multimodal system, and anatomical knowledge of these white matter pathways should be mastered before performing temporal surgical interventions. Furthermore, the surgical strategy and preoperative planning should be discussed considering the relationship between the lesion and white matter pathways, thereby reducing neurosurgical morbidity and mortality.